Еhe development of deliberative democracy and post-communist polish experience (some remarks) - Sokalska, Edyta (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The concepts of deliberative democracy, which emerged on a large scale in the 1980s, has become the subject of the scientific discussion on various fields. The flaws of representative democracy and the lack of legitimization of political systems led to the development of research on the improvement and modification of quality of democracy. Participatory democracy emphasized the broad participation of citizens in decision-making process, while deliberative (discursive) democracy indicated deliberation as essential, where political decisions should have been the product of fair and reasonable discussion and dialogue. The fall of communism and the elimination of some considerable threats connected with this kind of political regime brought the different attitude to the liberal democracies in post-communist states. Political changes in Poland in the late 80s and 90s of the 20th century led to the development of the new political regime. That process concerned the decentralization of powers, and consequently led to the creation of a new civil society, where local self-government was reintroduced by the reforms of public administration. The main institutions improving the development of the Polish civic society at the local level became local election, referendum, social consultations, civil (participatory) budget, and the possibility of civil participation in the debate on the report referring to the condition of the local administrative unit, and the civil legislative initiative.